How to read literature like a professor : a lively, and entertaining guide to understanding literature, from the Great Gatsby to the Hate U Give - Foster, Thomas C. (HarperPerennial, 2024)
"A thoroughly revised and expanded edition of Thomas C. Foster's classic guide--a lively and entertaining introduction to literature and literary basics, including symbols, themes and contexts, that shows you how to make your everyday reading experience more rewarding and enjoyable. While many books can be enjoyed for their basic stories, there are often deeper literary meanings interwoven in these texts. How to Read Literature Like a Professor helps us to discover those hidden truths by looking at literature with the eyes--and the literary codes--of the ultimate professional reader, the college professor. What does it mean when a literary hero is traveling along a dusty road? When he hands a drink to his companion? When he's drenched in a sudden rain shower? Ranging from major themes to literary models, narrative devices and form, Thomas C. Foster provides us with a broad overview of literature-a world where a road leads to a quest, a shared meal may signify a communion, and rain, whether cleansing or destructive, is never just a shower--and shows us how to make our reading experience more enriching, satisfying, and fun. This revised edition includes new chapters, a new preface and epilogue, and incorporates updated teaching points that Foster has developed over the past decade. Foster updates his classic text with more writers and books in the contemporary pantheon, including: Angie Thomas's The Hate U Give, Emily St. John Mandel's Station Eleven, Neil Gaiman's Neverwhere, Elizabeth Acevedo's The Poet X ), Helen Oyeyemi's Mr. Fox and Boy, Snow, Bird, Sandra Cisneros's The House on Mango Street, Zora Neale Hurston's Their Eyes Were Watching God, Maggie O'Farrell's Hamnet, Madeline Miller's Circe, Pat Barker's The Silence of the Girls, and Tahereh Mafi's A Very Large Expanse of Sea"--